Melanin nanoparticles as an endogenous agent for efficient iron overload therapy. Issue 45 (26th October 2016) - Yan, Junjie; Ji, Yu; Zhang, Pengjun; Lu, Xiaomei; Fan, Quli; Pan, Donghui; Yang, Runlin; Xu, Yuping; Wang, Lizhen; Zhang, Lei; Yang, Min
Abstract : Melanin was an efficient endogenous agent for iron-overload therapy in living mice due to its native biocompatibility, biodegradability and high iron-capturing volume. Abstract : Improving iron-chelating drugs for the safe and efficient therapy of iron overload disease is greatly challenging and highly desired. Endogenous iron chelators are perfect candidates because of their intrinsic biodegradability and biocompatibility, which avoid the severe side effects of the exogenous drugs currently present in clinical applications. Herein, for the first time, we have reported simply using melanin nanoparticles as an efficient natural nano-drug for iron overload therapy in living mice. Its native biocompatibility, biodegradability, high iron-capturing volume and long circulation time endow it with a lower required dosage quantity and frequency, but it accomplishes better therapeutic effects than the traditional drug deferoxamine (DFO).